2017
DOI: 10.1016/j.biopsych.2016.09.024
|View full text |Cite
|
Sign up to set email alerts
|

The Eating-Disorder Associated HDAC4 A778T Mutation Alters Feeding Behaviors in Female Mice

Abstract: Background While eating disorders (EDs) are thought to result from a combination of environmental and psychological stressors superimposed on genetic vulnerability, the neurobiological basis of EDs remains incompletely understood. We recently reported that a rare missense mutation in the gene for the transcriptional repressor histone deacetylase 4 (HDAC4) is associated with the risk of developing an ED in humans. Methods To understand the biological consequences of this missense mutation, we created transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 32 publications
0
25
1
Order By: Relevance
“…No GWAS of BN or BED have been conducted to date. In addition to GWAS approaches, familial linkage analysis with whole‐genome and exome sequencing has identified two potential missense mutations (Cui et al, ), which evidences a connection with eating‐disordered behaviours in a recent mouse model (Lutter et al, ). Environmental factors play a role in eating disorder risk. …”
Section: Truth 7: Genes and Environment Play Important Roles In The Dmentioning
confidence: 99%
See 1 more Smart Citation
“…No GWAS of BN or BED have been conducted to date. In addition to GWAS approaches, familial linkage analysis with whole‐genome and exome sequencing has identified two potential missense mutations (Cui et al, ), which evidences a connection with eating‐disordered behaviours in a recent mouse model (Lutter et al, ). Environmental factors play a role in eating disorder risk. …”
Section: Truth 7: Genes and Environment Play Important Roles In The Dmentioning
confidence: 99%
“…More sophisticated analytic techniques that examine the interplay between genetic risk and family environment indicate that the fit between an individual's genotype and his or her family environment may be relevant for eating disorder risk (Culbert et al, ). For example, following a report of a rare missense mutation being associated with the development of eating disorders, Lutter et al () found that group‐housed (vs. individually housed) transgenic female mice displayed irregular feeding and anxiety behaviours, preliminarily revealing both sex‐specific and gene‐by‐environment effects. In human studies, large samples using genome‐wide and phenome‐wide data are required for credible conclusions.…”
Section: Truth 8: Genes Alone Do Not Predict Who Will Develop Eating mentioning
confidence: 99%
“…Hdac4 A778T point mutant knock-in mouse was generated by introducing Hdac4 A778T mutation that correspond to human HDAC4 A786T mutation ( Figure 1A) by CRISPR technology as previously reported (Lutter et al, 2017). Heterozygous mice with mixed C57BL/6 and 129/Sv genetic background were further backcrossed to C57BL/6 female mice until reach over 98% of C57BL/6 background.…”
Section: Generation Of Hdac4 A778t Micementioning
confidence: 99%
“…In the followup mouse studies, we found that Esrra knockout mice display behavioral deficits relevant to EDs, including reduced food intake, decreased motivation to work for high-fat diet (HFD), and social subordination (Cui et al, 2015). Furthermore, mice heterozygous for Hdac4 A778T [corresponding to the human HDAC4 A786T mutation which we previously reported to be a gain-of-function mutation in the catalytic domain of HDAC4 to increase gene suppression in cultured cells ] on a mixed C57BL/6 and 129/Sv genetic background display altered feeding behaviors depending on housing condition (Lutter et al, 2017). In order to definitively evaluate the biological consequence of Hdac4 A778T mutation, here we performed a comprehensive behavioral characterization in homozygous Hdac4 A778T mice that we further backcrossed onto C57BL/6 background till reach over 98% of purity.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently identified the first 2 rare, highly penetrant genetic variants that increase the risk of developing an EDs [55]. Importantly, mice that are genetically manipulated to replicate the disease-associated human variants display several behavioral phenotypes relevant to EDs, including decreased willingness to work for a high-fat diet after being fasted overnight [56,57]. These mouse lines with impaired behavioral responses to a negative energy state are the first monogenic models of AN and offer a unique opportunity for screening of novel pharmaceutical compounds.…”
Section: Preclinical Models Of Restricted Eatingmentioning
confidence: 99%